The complete chloroplast genome sequence of Quercus myrsinifolia (Fagaceae) - Li, Yao (Mitochondrial DNA B Resour, 2019)
Quercus myrsinifolia Blume is an evergreen oak tree species native to East Asia, and is also one of the dominant trees of subtropical evergreen broad-leaved forests. In this study, we sequenced and analysed the complete chloroplast (cp) genome of the species. The circular genome is 160,803 bp in size, consisting of two copies of inverted repeat (IR) regions of 25,840 bp, one large single-copy (LSC) region of 90,223 bp, and one small single-copy (SSC) region of 18,900 bp. It encodes a total of 114 unique genes, including 80 protein-coding genes, 30 tRNA genes, and four rRNA genes. Phylogenetic analysis based on 30 cp genome sequences indicated that Q. myrsinifolia was among the members of section Cyclobalanopsis, and was most closely related to Q. sichourensis.